Search 72,490 tutors
FIND TUTORS
Ask a question
0 0

Linear Equations

Tutors, please sign in to answer this question.

1 Answer

5x + y = 1 ..... (1) 3x + y = 3 ..... (2)
Let's solve (1) for "y":
y = 1 - 5x , and substitute "y" in (2) by (1 - 5x)
3x + (1 - 5x) = 3
3x + 1 - 5x = 3 ---> -2x = 2 ---> x = -1
Now, we have to replace "x" by its value in one of two equations in order to find value of "y"
5(-1) + y = 1 ---> y = 5 + 1 ---> y = 6

The answer is pair of numbers (-1, 6) and system is consistent and independent.

Ashburn algebra 1 tutors